Kajian Literatur tentang Efektivitas Pembelajaran Berdiferensiasi dalam Pembelajaran IPAS di Sekolah Dasar - Avivah F. Az-zahra; Riri Syadira; Adrias Adrias; Salmaini Safitri Syam (Lembaga Pengembangan Kinerja Dosen, 2025)
In the elementary school curriculum that combines science and social studies learning into a single unit, namely science, differentiated learning is expected to be able to increase student understanding and support the improvement of learning outcomes because it adjusts the learning process according to the needs, interests, and individual potentials of students. This article aims to examine the effectiveness of differentiated learning in social studies learning through a literature review of various studies conducted between 2020 and 2025. This study reveals that the application of differentiated learning can improve the cognitive understanding, activeness, and analytical thinking skills of students in social studies learning.